Experiences and Perceived Outcomes of a Grocery Gift Card Program for Low-Income Households at Risk of Food Insecurity. (14th June 2022) - Lee, Yun Yun; Caron-Roy, Stéphanie; Turko, Bobbi; Shearer, Jane; Barker, Donald; Campbell, David; Elliott, Charlene; Raine, Kim; Tyminski, Sheila; Olstad, Dana
Abstract: Objectives: Household food insecurity negatively affects children's diet quality, physical and mental health, and academic performance. I Can for Kids' (IC4K) grocery gift card (GGC) program provides GGC to low-income households with school-aged children at risk of household food insecurity in Calgary, Canada. This study described program recipients' and facilitators' experiences and perceived outcomes of accessing or facilitating IC4K's GGC program. Methods: This study used qualitative descriptive methodology. Data generation and analysis were guided by Freedman et al's theoretical framework of nutritious food access. Semi-structured interviews were conducted between August and November 2020 with 37 program recipients and 17 program facilitators who were purposively recruited. Directed content analysis was used to analyze the data using a deductive-inductive approach. Codes were combined into subthemes and themes that summarized program recipients' and facilitators' experiences and perceived outcomes of receiving or distributing GGC, and suggestions to improve IC4K's GGC program. Results: Three themes were generated from the data: 1) IC4K's GGC program promoted a sense of autonomy and dignity among program recipients; 2) recipients used GGC to purchase foods that improved household dietary patterns and food skills, including foods that aligned with health-related food needs and cultural foodways and; 3) program logistical strengths and limitations, including the program's impact on facilitators' connection with clients and their workload, experiences of differential access to GGC among recipients, and the importance of increasing program awareness to reach more food insecure households. Conclusions: IC4K's GGC program enhanced recipients' access to nutritious foods, had positive impacts on household finances and diet quality, as well as recipients' social health and emotional wellbeing. However, differential access to GGC among recipients was also identified. Study findings were used to inform three recommendations to improve IC4K's GGC program: 1) increase the number of GGC that recipients can receive; 2) establish concrete guidelines governing GGC distribution and; 3) increase program awareness. Funding Sources: O'Brien Institute for Public Health.